NFLUENCE OF INITIAL CONCENTRATION OF FUEL ON BURNING OF LAMINAR AND TURBULENT JETS - Askarova, A.S.; Bolegenova, S.A. (Recent Contributions to Physics, 2021)
The numerical decision of a problem on burning the laminar and turbulent flooded jets of metane in a motionless environment is received.